Application of analytic hierarchy process to determine and optimize FDM printing process parameters for tensile strength - Maidin, Shajahan; Sah Azmi, Amira Atiqah; Md Nor hayati, Norilani; Mohammed Al Balushi, Mohammed Haroun (Penerbit UTM Press, 2022)
This paper investigates the application of the analytic hierarchy process (AHP) to optimize Fused Deposition Modeling (FDM) printing process parameters to obtain the best tensile strength from several test specimens. To proceed with applying the AHP, the data to list the most effective process parameters that affect the tensile strength was collected from various journals. After obtaining the best option from the AHP analysis, a tensile strength test was conducted to validate the data. Standard ASTM specimen with a gauge length of 57 mm and a gauge width of 13mm and the material specimen of Polylactic Acid (PLA) was printed using an open-source FDM printer. The result shows that from the AHP, option 3 has the highest score of 0.7723, and the best process parameter for tensile strength of the FDM process is layer thickness of 0.3mm, infill density of 80%, build orientation of 00, and raster angle of 600. Finally, to validate the result from the AHP, the tensile strength test of option 3 was done, and it shows that option 3 has the highest tensile strength, which is 2556 N/m2 compared to the other two options. This study is significant because it shows that AHP is feasible to obtain the optimum proses parameters that influence the mechanical properties of the printed test specimens